Islamic Social Reporting Disclosure: The Role of Audit Committee and Institutional Ownership - Maya Indriastuti; Anis Chariri (The Indonesian Journal of Accounting Research, 2022)
In Islam, social responsibility is part of worship to create a balance in human social relations. It means that the public has the right to know various information about the activities of companies that have relations with the public. This is a form of corporate responsibility to the community, whether the activities achieve the goals that have been set are following sharia and do not harm the surrounding community. This study aims to determine the effect of the audit committee and institutional ownership on ISR disclosure (ISRD) at 70 annual financial reports of 14 companies on the Jakarta Islamic Index from 2015-2019. All data in this study were processed by multiple linear regression analysis. The results show that the audit committee does not affect the ISRD. At the same time, institutional ownership can improve the ISRD. These results indicate that a company's small number of audit committees does not affect the ISRD. On the contrary, the higher the institutional ownership ratio, the higher ISRD. ISRD becomes a media of communication, a form of commitment, and corporate responsibility in maintaining good relations and trust on an ongoing basis to gain support from stakeholders to realize the company's goals. In addition, the ISRD can also positively impact the company, attracting investors' attention to investing and assisting decision-making for stakeholders and Muslim companies to fulfill their obligations to Allah SWT and society.